Antioxidant Activities in vitro of Water and Liposoluble Extracts Obtained by Different Species of Edible Insects and Invertebrates - Di Mattia, Carla; Battista, Natalia; Sacchetti, Giampiero; Serafini, Mauro (Frontiers in Nutrition, 2019)
A new global interest in entomophagy, the practice of eating insects, arise from the impellent necessity of preserving agriculture resources and to obtain a drastic reduction of the ecological impact of animal food on the planet. The composite nutritional content, direct consequences of a plant-based feeding, associated with the undoubtedly ecological properties, suggest for insects a role as sustainable and functional foods. We aim to investigate the ability of water and liposoluble extracts, obtained by fourteen commercially available edible insects, to display an antioxidant effect in vitro. Results show that water-soluble extracts of grasshoppers, silkworm and crickets display the highest values of antioxidant capacity (TEAC), fivefold higher than fresh orange juice, while giant cicada, giant water bugs, black tarantula and black scorpions have negligible values. Grasshoppers, africa caterpillars and crickets have the highest levels of reducing power (FRAP), double than fresh orange juice. Grasshoppers, black ants and mealworms contain the highest levels of total polyphenols, while black tarantula, black scorpions and giant water bugs are positioned at the bottom of the ranking. The liposoluble fraction of silkworm, giant cicada and africa caterpillars shows highest level of TEAC, twice than olive oil, while black tarantula, palm worm and black ants are placed in the bottom of the ranking. Edible insects represent a potential source of antioxidant ingredients with an efficiency related to their taxonomy and eating habits. More evidences are needed in order to understand if the practice of eating insects might contribute to modulate oxidative stress in humans.